Case report: Recovery of long-term delayed complete atrioventricular block after minimally invasive transthoracic closure of ventricular septal defect - Lu, Jin; Lian, Xingchen; Wen, Ping; Liu, Yuhang (Frontiers in Cardiovascular Medicine, 2023)
Introduction Long-term delayed complete atrioventricular block (CAVB) is a serious complication of ventricular septal defect (VSD) closure treatment. Thus, cardiac surgeons have made significant efforts to explore its causes and reduce its incidence. In recent years, minimally invasive transthoracic closure (MITC) of VSD has been used widely and successfully in China as it is easy to repeat, ensures individualized closure, and can be debugged repeatedly. Theoretically, the possibility of the recurrence of CAVB is lower than that with transcatheter closure. Although the incidence of CAVB after MITC of VSD is inevitable, long-term delayed CAVB has rarely been reported. Case description Herein, we report a case of delayed CAVB that occurred 2 years and 5 months after performing MITC of a perimembranous VSD. The cardiac rhythm recovered after the occluder was removed surgically. Conclusion The findings of our case report emphasize that since delayed CAVB may occur in the long term after MITC of VSD, the safety of MITC of VSD should be reassessed, the indications for MITC should be strictly followed, and long-term follow-up, including lifelong follow-up, is recommended for patients postoperatively. In addition, the occluder should be removed surgically in patients with CAVB as it may restore normal heart rhythm.